Does central bank independence really matter? Re-assessing the role of the independence of monetary policy-makers in macroeconomic outcomes. (31st October 2014) - Zervoyianni, Athina; Anastasiou, Athanasios; Anastasiou, Andreas
Despite the growing literature, central bank independence (CBI) is still one of the most controversial and frequently discussed issues in macroeconomics. This paper re-examines the role of central bank independence in macroeconomic outcomes, seeking to add to the existing empirical literature in two ways: first, we control for factors, which might account for the cross-country differences in macroeconomic outcomes, but which, either individually or as a group, are often given no adequate attention in existing studies; second, in addition to standard regressions, we use Markov-Chain Monte-Carlo estimation methods from a Bayesian perspective, which are believed to improve result robustness by increasing parameter accuracy and reducing the effect of outlying observations. Based on (average) data from 39 countries covering the time-periods 1981–1989, 1991–1998 and 1999–2006, our estimates suggest that lower inflation should be seen as resulting from a broad range of institutional and structural factors, with CB independence failing to play the key role. We also find no consistent evidence of a positive relationship between central bank independence and employment growth or evidence that it reduces economic instability.